The Saint Prosper Monastery in the Fourteenth Century: Management and Relational Aspects (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
The aim of this paper is to illustrate the management of the properties and the relational network of the monastery of S. Prospero in Reggio Emilia during the 14th century. The analysis of an unpublished source allow us to see how different causes of the Crisis of the 14th century (economic, social, demographic and political) affected the monastery, showing aspects of continuity and discontinuity. On one hand continuity can be spotted in the relational network gravitating around the abbey, consisting of both rural and urban population. The members of the urban oligarchy in order to establish deep roots in the monastery of S. Prospero used to receive monastic lands in feud or in leasing. On the other hand, discontinuity can be obviously spotted in the agrarian contracts. Under the pressure of economical (increasing the land’s yield and compacting the farms) and political needs (restoring the relational network after the Black Plague and the Feltrino Gonzaga’s government) the agrarian contracts reduced their duration, from long time ones to short ones, and sometimes they added new clauses, whose aim was to increase the dependency between the abbot and the peasants.DOI 10.17464/9788867743322
Keywords: Reggio Emilia; San Prospero; crisis of the 14th century; conjuncture of the 14th century; benedictine monastery